BEBERAPA ASPEK PERBINCANGAN SEJARAH DALAM MAJALAH PENGASUH SEKITAR TAHUN 80-AN - Abdul Hamid, Faisal@Ahmad Faisal (Journal of Al-Tamaddun, 2005)
Numerous historical writings were written in 'Pengasuh' in the 1980s. This article discusses two historical aspects of 'Pengasuh' during that period which are the ulama' (scholar) of Pengasuh and the history of mosque. With regard to the ulama'of Pengasuh, Dato'Haji Ismail Yusoff and Dato'Muhammad bin Che Wook have been chosen as the focus of our discussion. Meanwhile, for the history of mosque section, Muhammadi Mosque in Kota Bharu and Wadi Husairu mosque in Narathiwat, Thailand have been chosen as our focus.